Safety and efficacy of a feed additive consisting of endo‐1, 4‐β‐xylanase produced by Bacillus subtilis LMG S‐15136 (Belfeed B MP/ML) for sows in order to have benefits in piglets and for all porcine species (Beldem, a division of Puratos NV). (5th March 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Belfeed B MP/ML as a feed additive for sows in order to have benefits in piglets. The additive is to be used in to sows in order to have benefits in piglets and to all porcine species at any developmental stage at 10 IU/kg feed. This additive consists of endo‐1, 4‐β‐xylanase produced by a genetically modified strain of Bacillus subtilis (LMG S‐15136). In a previous opinion, the FEEDAP Panel could not conclude on the safety of the additive for the users regarding the potential of the additive as dermal sensitiser and on the efficacy of the additive when added to feed for sows in order to have benefits in piglets. In the absence of new information, the FEEDAP Panel retained its previous conclusion that the additive is not irritant to skin or eyes but should be considered a respiratory sensitiser. No conclusions could be drawn on its potential to be a dermal sensitiser. The applicant provided new efficacy data and complementary information regarding a previous study. Based on the previously assessed data and the newly submitted ones, the Panel concludes that although the additive has a potential to be efficacious as a zootechnical additive in sows during the lactation period at the level of 10 IU/kg feed, the data are considered not sufficient to conclude on a beneficial effect on the performance of the litters.